Optimal democratic mechanisms for taxation and public good provision - Felix Bierbrauer; Marco Sahm (Max Planck Institute for Research on Collective Goods, 2008)
We study the interdependence of optimal tax and expenditure policies. An optimal policy requires that information on preferences is made available. We first study this problem from a general mechanism design perspective and show that efficiency is possible only if the individuals who decide on public good provision face an own incentive scheme that differs from the tax system. We then study democratic mechanisms with the property that tax payers vote over public goods. Under such a mechanism, efficiency cannot be reached and welfare from public good provision declines as the inequality between rich and poor individuals increases.
Keywords: H41; D71; D72; D82; 330; Public goods; optimal taxation; two-dimensional heterogeneity; asymmetric information; Optimale Besteuerung; Finanzpolitik; Öffentliches Gut; Allokationseffizienz; Ökonomische Theorie der Demokratie; Wahlverhalten; Asymmetrische Information; Theorie